Catalytic Biomass Processing: Prospects in Future Biorefineries - Luque, Rafael (Current Green Chemistry, 2015)
Biomass can efficiently replace petroleum in the production of fuels for the transportation sector. One effective strategy for the processing of complex biomass feedstocks involves previous conversion into simpler compounds (platform molecules) which are more easily transformed in subsequent upgrading reactions. This contribution is aimed to provide a short overview on biomass characteristics and processing chemistries illustrated by some examples from the group related to relevant catalytic strategies for biorefineries.
Keywords: Biomass valorization